Compatibilisation of various PLA/thermoplastic elastomer blends with diisocyanate coupling agent. (16th March 2018) - Vuillaume, Pascal Yves; Vachon, Andro; Grey, William; Pépin, Keven; Zhang, Chan Juan
ABSTRACT: Poly(lactic acid) (PLA) is characterised by its inherent brittleness, a detrimental feature for the production of durable bioplastics. PLA has been toughened by a low amount (12 wt-%) of various thermoplastic elastomers (TPE) including poly(ether-b-ester) (PEEs), poly(ether-b-amide) (PEBA) and poly(ether-b-urethane) (PEU). PLA–TPE blends were prepared by using a twin screw extruder. Ductility and impact resistance can be slightly improved with the incorporation of TPEs but but PEBA appears the most efficient. Reactive compatibilisation has been performed with the addition in the melt of a low amount (2 wt-%) of 4, 4-methylene diphenyl diisocyanate. All compatibilised blends exhibit high toughness with similar ductility. These blends preserve good stiffness and high tensile strength. Compatibilised PEBA blends can be considered as super tough poly(lactic acid) materials. This work confirms that the flexibility of the elastomer together with the quality of the interfacial adhesion between the rigid (PLA) and the soft (TPE) phases are the primary factors influencing the toughness.